The Imperfection in a Firm’s Knowledge of the Transformation Process Among Interlinked Internal Networks: The Defect Case - Cris Kuntadi; Prasetyo Boeditjahjono Boeditjahjono; Yuli Permatasari; Meylia Candrawati (Gadjah Mada International Journal of Business, 2020)
This study, firstly, identifies and analyzes the supply chain management of Aseli Dagadu Djokdja, Co., Ltd., (here-after ADD) which has a problem. Secondly, this study pinpoints what causes the problem in ADD’s supply-chain management (SCM). Thirdly, it investigates ADD’s knowledge of the transformation process, since it was not conducted properly. This research chose to use an exploratory case study with an in-depth interview to collect the data. This article questions all the CEOs and observes all stages of activity accompanied by their information, resources, and financial flows. The interviewer applies angulations to two or more of the subjects. This study takes note that ADD’s knowledge of the transformation process  is imperfect; this weakness is at the top managerial level. The problem is also found when oral explanations do not follow the transfer of documents among the divisions and staff. It means that information asymmetry takes place. This study, which is designed with SNT and a comprehensive knowledge of the transformation process, has several biases. The first one is the inference validity bias. Secondly, it did not investigate how ADD’s management faces industrial competitiveness. Finally, this research could not capture what the staff at ADD transforms their knowledge into.